Research steps in qualitative study implementation - Maja Račić; Milena Dubravac-Tanasković; Janja Bojanić; Biljana Mijović; Slobodan Stanić (Биомедицинска истраживања, 2018)
Public health represents a field full of unresolved issues which are often raised by highly complex and mutually related events. Due to this, the more frequent use of qualitative scientific research is required. Qualitative research is primarily focused on the world view of an individual or a group, enabling them to form attitudes and practise related to certain research questions. As its final goal is to comprehend some aspects of social life, qualitative study analyzes words instead of numbers, which makes the interpretation of results complicated. In several simple steps, this paper will allow us to understand qualitative research methodology by providing basic insight into research question formulation, sample selection and methods of data collection and analysis.
Keywords: qualitative research; methodology; research steps